Quality of Life of Family Caregivers of Patients with Mental Illness in a Hospital - Karna , Anjani; Adhikari , Rajdevi; Bhattarai , Tilarupa (Journal of Biratnagar Nursing Campus, 2025)
Background: Quality of Life (QOL) is a measure of a person's functional capacity and overall health. Those who provide care for people with mental illnesses have reported a lower quality of life. Caregivers of mentally ill patients often experience higher levels of stress, psychological problems, social isolation, and family conflict. This study aimed to evaluate QOL for individuals caring for people with mental illness.Method: A descriptive cross-sectional study design was used. A total of 264 caregivers from the Mental Hospital's Psychiatric Outpatient Department in Lagankhel were selected using a non-probability purposive sampling technique. Data were collected from BS 2079/04/22 to 2079/05/18 using a structured questionnaire. The WHOQOL BREF Questionnaire and questions about sociodemographic and mental health factors were included in the interview questionnaire. Data were analyzed using descriptive and inferential statistics version 16.Results:  findings of the study showed that 44.3% of respondents had poor QOL, while 55.7% had good QOL. QOL was associated with several demographic factors, including patient age group (p = 0.035), sex (p = 0.030), and disease type (p = 0.038). Additional associations were observed with caregiver age group (p = 0.017), sex (p = 0.018), education (p = 0.043), and relationship with patients (p = 0.0009).Conclusion: Caregivers’ QOL was lower in the social domain and higher in the physical domain. health care practitioners should pay attention to caregivers’ social needs to improve their overall quality of life.